Philippe Bunau-Varilla papers - Bunau-Varilla, Philippe, 1859-1940.
Correspondence, speeches, writings, legal records, newspaper clippings, and other papers concerning Bunau-Varilla's activities in the United States (1900-1907), his efforts relating to the Panama Canal, and his role in the Panamanian revolution and as minister plenipotentiary for the new government. Includes material pertaining to the Hay-Bunau-Varilla treaty of 1903 and an eyewitness account of volcanic activity in Nicaragua in 1902. Correspondents include Manuel Amador Guerrero, John Bigelow, Theodore E. Burton, Gustave Eiffel, William Crawford Gorgas, Mark Alonzo Hanna, John Hay, J.J. Jusserand, Ferdinand de Lesseps, Henry Cabot Lodge, and Theodore Roosevelt.
Panamanian diplomat and engineer.
Collection material in French and English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Amador Guerrero, Manuel, -- 1833-1909 -- Correspondence; Bigelow, John, -- 1817-1911 -- Correspondence; Burton, Theodore E. -- 1851-1929 -- Correspondence; Eiffel, Gustave, -- 1832-1923 -- Correspondence; Gorgas, William Crawford, -- 1854-1920 -- Correspondence; Hanna, Marcus Alonzo, -- 1837-1904 -- Correspondence; Hay, John, -- 1838-1905.; Hay, John, -- 1838-1905 -- Correspondence; Jusserand, J. J. -- 1855-1932 -- Correspondence; Lesseps, Ferdinand de, -- 1805-1894 -- Correspondence; Lodge, Henry Cabot, -- 1850-1924 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Panama. -- 1903 November 18.; Canals, Interoceanic; Diplomatic and consular service, Panamanian -- United States; Volcanoes -- Nicaragua; Panama -- History -- Revolution, 1903.; Panama -- Foreign relations -- United States; Panama -- Politics and government -- 1903-1946.; Panama Canal (Panama); United States -- Foreign relations -- Panama; Diplomats -- Panama; Engineers